BARONG LANDONG: FUNGSI DAN PELESTARIANNYA SEBAGAI IDENTITAS BUDAYA ORANG LEMBAK DI KOTA BENGKULU - Rois Leonard Arios (JURNAL PENELITIAN SEJARAH DAN BUDAYA, 2018)
Art of the people born from the community can be an identity for the community or a tribe if the art isstill used by the community. This research analyzes and describes barong landong as an art of Lembaktribe in Bengkulu City. The research is conducted by qualitative approach by interviewing the actorsinvolved in making, performing, and preservation efforts. The result of the research shows the changeof function of barong landong art. Functionally barong landong still exist but no longer become thecultural identity of the people of Lembak but already belongs to communal society Bengkulu.